Synergistic Activity between Two Antifungal Proteins, the Plant Defensin NaD1 and the Bovine Pancreatic Trypsin Inhibitor - Mark R. Bleackley (American Society for Microbiology, 2017)
ABSTRACT Defensins are a large family of small, cationic, cysteine-rich proteins that are part of the defense arsenal that plants use for protection against potentially damaging fungal infections. The plant defensin NaD1 from Nicotiana alata is a potent antifungal protein that inhibits growth and kills a variety of fungal pathogens that affect both plant and animal (human) hosts. Some serine protease inhibitors have also been reported to be antifungal molecules, while others have no inhibitory activity against fungi. Here we describe the synergistic activity of the plant defensin NaD1 with a selection of serine protease inhibitors against the plant pathogens Fusarium graminearum and Colletotrichum graminicola and the animal pathogen Candida albicans. The synergistic activity was not related to the protease inhibitory activity of these molecules but may arise from activation of fungal stress response pathways. The bovine pancreatic trypsin inhibitor (BPTI) displayed the most synergy with NaD1. BPTI also acted synergistically with several other antifungal molecules. The observation that NaD1 acts synergistically with protease inhibitors provides the foundation for the design of transgenic plants with improved resistance to fungal disease. It also supports the possibility of naturally occurring accessory factors that function to enhance the activity of innate immunity peptides in biological systems. IMPORTANCE This work describes the increased activity of a natural antifungal peptide in the presence of another antifungal peptide from a different family. This is termed antifungal synergy. Synergy is important for decreasing the amount of antifungal molecule needed to control the disease. Traditionally, naturally occurring antifungal molecules are assayed in isolation. Identification of synergistic interactions between antifungal peptides means that their activities in a complex biological system are likely to be different from what we observe when examining them individually. This study identified synergy between an antifungal peptide and a group of peptides that do not affect fungal growth in vitro. This provides the foundation for generation of transgenic plants with increased resistance to fungal disease and identification of antifungal accessory factors that enhance the activity of innate immune molecules but do not have an antifungal effect on their own.